Efficacy and Safety of Ciprofol for Sedation/Anesthesia in Patients Undergoing Hysteroscopy: A Randomized, Parallel-Group, Controlled Trial - Lan H; Shan W; Wu Y; Xu Q; Dong X; Mei P; Duan G; You M; Jin L; Wu J (Dove Medical Press, 2023)
Haiyan Lan, Weifeng Shan, Yini Wu, Qiaomin Xu, Xiaoli Dong, Peiyi Mei, Gongchen Duan, Minji You, Linfei Jin, Jimin Wu Department of Anesthesiology, Lishui City People's Hospital, The Sixth Affiliated Hospital of Wenzhou Medical University, Lishui, People's Republic of ChinaCorrespondence: Jimin Wu, Department of Anesthesiology, Lishui City People's Hospital, The Sixth Affiliated Hospital of Wenzhou Medical University, No. 15, Dazhong Street, Lishui, Zhejiang Province, 323000, People's Republic of China, Email wujimin2022@163.comObjective: To compare the efficacy and safety of ciprofol and propofol for sedation during hysteroscopy.Methods: A total of 149 patients undergoing hysteroscopy were randomly assigned to a ciprofol (Group C) or propofol group (Group P). All cases received intravenous sufentanil 0.1 μg/kg for analgesic preconditioning. Group C received an induction dose of ciprofol 0.4 mg/kg and a maintenance dosage of 0.6- 1.2 mg/kg/h to maintain BIS value between 40- 60. In Group P, propofol was started at 2.0 mg/kg and then maintained at 3.0- 6.0 mg/kg/h. The primary outcome was the successful rate of hysteroscopy. Secondary outcomes included the change of hemodynamic, respiratory adverse events, injection pain, body movement, recovery time, anesthetist's satisfaction, time of disappearance of the eyelash reflex and the incidence of nausea and vomiting.Results: The success rate of hysteroscopy in each group was 100%. After drug administration, the incidence of hypotension in Group C was much lower than that in Group P (P< 0.05). The incidence of respiratory adverse events in Group C (4.0%) was much lower than that in Group P (31.1%) (P< 0.05). The incidence of injection pain and body movement in Group C was significantly lower than that in Group P (P< 0.05). The mean eyelash reflex disappearance time was less than 3 minutes in both groups. There was no statistically significant difference between the two groups in awakening times, anesthetist's satisfaction and the incidence of nausea and vomiting. No serious adverse events occurred in any patients.Conclusion: Ciprofol proved to be a safer alternative to propofol for anesthesia during hysteroscopy. In comparison to propofol, ciprofol does not cause injection pain, exerts less impact on hemodynamics, and results in less respiratory depression.Keywords: ciprofol, propofol, sedation, anesthesia, hysteroscopy